Comparative risk of major cardiovascular events associated with second‐line antidiabetic treatments: a retrospective cohort study using UK primary care data linked to hospitalization and mortality records. Issue 9 (30th June 2016) - Zghebi, S. S.; Steinke, D. T.; Rutter, M. K.; Emsley, R. A.; Ashcroft, D. M.
Abstract : Aims: To examine the risk of major cardiovascular events associated with second‐line diabetes therapies, in patients with type 2 diabetes, after adjusting for known cardiovascular risk factors. Methods: This was a retrospective cohort study of patients prescribed second‐line regimens between 1998 and 2011 after first‐line metformin. The UK Clinical Practice Research Datalink, with linked national hospitalization and mortality data, for the period up to December 2013, was used. Inverse probability of treatment‐weighted time‐varying Cox regression models was used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for developing a major cardiovascular event (cardiovascular death, myocardial infarction, stroke, acute coronary syndrome, unstable angina, or coronary revascularization) associated with second‐line therapies. Analyses adjusted for patient demographic characteristics, comorbidities, glycated haemoglobin, socio‐economic status, ethnicity, smoking status and concurrent medications. Results: A total of 10 118 initiators of a second‐line add‐on to metformin of either a sulphonylurea (n = 6740), dipeptidyl peptidase‐4 (DPP‐4) inhibitor (n = 1030) or thiazolidinedione (n = 2348) were identified. After a mean (standard deviation) of 2.4 (1.9) years of follow‐up, 386, 36 and 95 major cardiovascular events occurred in sulphonylurea‐, DPP‐4 inhibitor‐ and thiazolidinedione‐initiators, respectively. In comparison with the metformin–sulphonylurea regimen, adjusted HRs were 0.78 (95% CI 0.55; 1.11) for the metformin–DPP‐4 inhibitor regimen and 0.68 (95% CI 0.54; 0.85) for the metformin–thiazolidinedione regimen. Conclusions: Thiazolidinedione add‐on treatments to metformin were associated with lower risks of major cardiovascular disease or cardiovascular death compared with sulphonylurea add‐on treatment to metformin. Lower, but non‐statistically significant, risks were also found with DPP‐4 inhibitor add‐on therapies.